2014
DOI: 10.1158/0008-5472.can-13-3494
|View full text |Cite
|
Sign up to set email alerts
|

Capillary-Wall Collagen as a Biophysical Marker of Nanotherapeutic Permeability into the Tumor Microenvironment

Abstract: The capillary wall is the chief barrier to tissue entry of therapeutic nanoparticles, thereby dictating their efficacy. Collagen fibers are an important component of capillary walls, affecting leakiness in healthy or tumor vasculature. Using a computational model along with in vivo systems, we compared how collagen structure affects the diffusion flux of a 1 nm chemotherapeutic molecule (doxorubicin [DOX]) and an 80 nm chemotherapy-loaded pegylated liposome (DOX-PLD) in tumor vasculature. We found a direct cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 40 publications
5
53
0
Order By: Relevance
“…We here emphasize that the goal of the paper was to formulate a computational framework for modeling complex problems such as convective-diffusive transport in organs or tumors, so that the presented results give basically a qualitative confirmation of the methodology. Quantitative verification of accuracy of models, which are incorporated into the methodology of this study, was partly given in our previous references [27,32,19,34], and the results are in agreement with general observations in experiments. We present two examples which demonstrate applicability of the developed computational model to two very different conditions, one is a tumor with extremely small dimensions and the other is an organ with an order-ofmagnitude larger dimensions and different material parameters.…”
Section: Implementation Of the Computational Modelsupporting
confidence: 82%
See 3 more Smart Citations
“…We here emphasize that the goal of the paper was to formulate a computational framework for modeling complex problems such as convective-diffusive transport in organs or tumors, so that the presented results give basically a qualitative confirmation of the methodology. Quantitative verification of accuracy of models, which are incorporated into the methodology of this study, was partly given in our previous references [27,32,19,34], and the results are in agreement with general observations in experiments. We present two examples which demonstrate applicability of the developed computational model to two very different conditions, one is a tumor with extremely small dimensions and the other is an organ with an order-ofmagnitude larger dimensions and different material parameters.…”
Section: Implementation Of the Computational Modelsupporting
confidence: 82%
“…can dominate the transport through the wall. This interaction on a molecular level may be incorporated into a continuum transport model by evaluation of the effective diffusion coefficients (or scaling functions) using MD procedures and a numerical homogenization (within a multiscale-hierarchical concept); such a multiscale model has been applied to various bioengineering problems [19,[27][28][29][30][31][32][33][34][35]. Briefly, the following steps are undertaken in formulating the multiscale model.…”
Section: Fundamental Equations For Transport Within Capillariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our in vivo and in silico study revealed that phenotypic differences of tumor microenvironment can negate enhanced PK properties of nanotherapeutics [3]. There, capillary collagen of type-IV can be a biophysical marker determining the extravasation of doxorubicin (DOX) by using its liposomal formulation (PLD) as a nanotherapeutic formulation of DOX.…”
Section: Drug Delivery and Tumor Microenvironmentmentioning
confidence: 94%